Kajian Faktor Organisasi dengan Kinerja Perawat Pelaksana dalam Pendokumentasian Asuhan Keperawatan di Ruang Rawat Inap RSUD Pariaman : Study of Organizational Factors with Implementing Nurses' Performance in Nursing Care Documentation in the Inpatient Room of Pariaman Hospital - Dewi Murni; Hafni Bachtiar; Happi Sasmita (NERS Jurnal Keperawatan, 2016)
Nursing care documentation is a record and report in nursing setting that is useful for patients, nurse and medical team in providing services on communication accurately and completely in writing as nurse’s responsibility. An effective documentation could ensure the continuity of service, saving time and minimizing the risk of error. The implementation of nursing documentation is one way to measure , determine, monitor and conclude a nursing care service in a hospital. The implementation of nursing documentation in Pariaman Public Hospital shows are still low (49.5%) than their own limit 65%, while, according to the Ministry of Health, 80% as the limit. Nurse’s performance in the nursing care implementation was influenced by organizational factors (Leadership of head nurse, remuneration, supervision and coaching). The purpose of this study was to find out whether organizational factors related to nurses' performance in the implementation of nursing care in hospitals Pariaman. This study used cross sectional design. Population and sample in this study were 89 nurses in hospitals Pariaman, with simple random sampling. Instrument used questionnaire. The results showed that there was a significant relationship between leadership (p = 0.000), rewards (p = 0.005), supervision (p = 0.000) and coaching (p = 0.003). This study recommended to the head of Pariaman Public Hospital to improve supervision in each room, leadership, rewards and guidance on the implementation of nursing care to nurses.